Assessing the competency of University of Malaya dental graduates: employers' and graduates' perceptions. - Razak, I.A.; Latifah, R.R.J.; Jaafar, N.; Abu Hassan, M.I.; Ab Murat, N. (American Dental Education Association, 2008)
A survey was conducted to assess competencies of dental graduates of the Faculty of Dentistry, University of Malaya, as perceived by the graduates and their employers, based on the five-year undergraduate curriculum introduced in 1995. All senior dental officers in the Ministry of Health (MOH), representing employers, and all 164 dental graduates of the years 2000, 2001, and 2002 were sent a self-administered questionnaire covering eight areas of competency. The respondents had to rate these areas on a scale of 1 (very poor) to 4 (very good). The responses for each area were then dichotomized into poor (1 and 2) and good (3 and 4). If less than 60 percent of the respondents rated an area as good, then it was categorized as needing attention; 60-69 percent as satisfactory; and 70 percent and above as excellent. One hundred and six graduates (64.6 percent) and twenty-nine employers (96.7 percent) responded; of the graduates, 73.6 percent were working in the MOH and 22.6 percent in private practice. About 57.1 percent of employers reported that at least five graduates have worked under them. Graduates (85.7 percent) and employers (83.3 percent) agreed that graduates have excellent skills in communication. Although all graduates perceived their competency to be excellent in the four areas (treatment planning; community-based skills; management, administrative skills, and personal management; and professional development skills), employers felt that these are the areas that are of concern and needed attention. In conclusion, whilst generally the graduates' level of competency in almost all areas is acceptable or good, there are areas of concern that need to be addressed to further improve the five-year curriculum at the University of Malaya.